Ralph Compton : [large type] : Nowhere, TX - Compton, Ralph (Thorndike Press, 2004)
Nowhere, Texas, is a haven for cutthroats and thieves, but its citizens have had enough of their unwanted guests. Now it's time to put Nowhere on the map.